An Empirical Review of Determinants Influencing Firm Collaboration and Their Impact on Competitive Performance - Dody Suhermawan; Yeni Ika Pratiwi; Mahjudin Mahjudin (PT. Mawadaku Sukses Solusindo, 2025)
Achieving a sustainable competitive advantage is essential for improving marketing performance in highly dynamic business environments. One strategic approach to attaining this objective is through relationship learning, which enables firms to enhance their organizational learning capabilities by facilitating systematic information exchange, fostering shared learning platforms, and aligning behaviors with stakeholder expectations. Relationship learning is not limited to dyadic firm-stakeholder interactions but also encompasses insights obtained from external sources such as scientific publications and academic research. By integrating both internal and external knowledge, firms can develop a comprehensive understanding of their strategic environment, allowing them to formulate more adaptive and effective marketing strategies. The establishment of mutual understanding through continuous collaborative efforts between customers and suppliers serves as a foundation for influencing behavioral alignment and strategic coherence. This dynamic learning process significantly contributes to the development of a firm’s competitive advantage, thereby strengthening its marketing performance over time.